Echocardiography and laboratory outcomes of COVID-19 in children with a history of Kawasaki disease: a preliminary observation - Guo, Mindy Ming-Huey; Chang, Ling-Sai; Chen, Yu-Jhen; Kuo, Ho-Chang (Frontiers in Cardiovascular Medicine, 2023)
Background Infection with SARS-CoV-2 virus has been associated with cardiovascular sequelae including multisystem inflammatory syndrome (MIS-C) in children. Patients with a prior history of Kawasaki disease, may be more susceptible to changes in echocardiographic or laboratory findings after COVID-19. The objective of this study was to investigate the echocardiographic and laboratory findings in children with a prior history of Kawasaki disease after SARS-CoV-2 infection. Materials and methods In this study, we performed a retrospective chart review of 41 children younger than 18 years old who were diagnosed with COVID-19 from April to August of 2022 and had a prior history KD. We included echocardiography and blood draw data obtained at the last outpatient follow-up at our hospital for KD, and within 4 months of SARS-CoV-2 infection. Echocardiographic data obtained from 82 age-matched and gender matched controls were also included for comparison. Results We found that COVID-19 resulted in slightly higher RCA Z-scores within the first month after infection (mean ± SE, 1.20 ± 0.18 vs. 0.83 ± 0.18, p = 0.030), although this increase did not result in coronary artery dilatation, defined as a Z-score of at least 2.5. In addition, we found that degree of RCA dilatation after COVID-19 infection was negatively correlated with the change in monocyte percentage (Pearson's correlation coefficient—0.363, p = 0.020). Moreover, RCA Z-score changes were lower in patients who received at least one dose of mRNA COVID-19 vaccine when compared those who did not receive any (mean ± SE, −0.23 ± 0.16 vs. 0.39 ± 0.17, p = 0.031). Conclusion In this pilot study we found that COVID-19 infection resulted in slightly higher RCA Z-scores in children with a prior history of KD, although not large enough to be classified as coronary aneurysms. While these changes could be the result of measurement imprecision or interobserver variation, further study of the cardiac outcomes of COVID-19 infection in children with a prior history of KD are needed in the future.